Dukungan Keluarga dengan Kejadian Demensia pada Lansia - Adila, Adila Nurdefianty; Suhermi; Ramli, Rahmawati; Andi Yuliana (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2024)
Dementia is one of the global health problems with a total of more than 55 million cases in the world and more than 60% of them live in low to middle class countries. Adequate family support will inhibit the decline in cognitive function.This study aims to determine whether there is a relationship between family support and the incidence of dementia in the elderly in the working area of ​​the Bontomarannu Health Center. The design used in this study is descriptive analytic using a cross-sectional study approach. The sample included in this study was random sampling with a sample of 60 respondents. The test used in this research is using chi square. The results of this study indicate that family support for moderate family dysfunction is 67% compared to severe family dysfunction 10% and good 23%, severe cognitive impairment is 43% more than with 30% moderate cognitive impairment and 27%. There is a significant relationship between the relationship between family support and the incidence of dementia in the elderly in the Bontomarannu Community Health Center (p value 0.001 < 0.05). The conclusion of this study is that there is a relationship between family support and the incidence of dementia in the elderly in the Bontomarannu Community Health Center. Therefore, it is hoped that the puskesmas can increase counseling to families about the importance of providing support to the elderly and then for the elderly and their families to be active in participating in posyandu activities, and routinely conducting health checks.